A novel enhanced dot blot immunoassay using colorimetric biosensor for detection of Toxoplasma gondii infection. (December 2021) - Safarpour, Hanie; Pourhassan-Moghaddam, Mohammad; Spotin, Adel; Majdi, Hassan; Barac, Aleksandra; Yousefi, Mehdi; Ahmadpour, Ehsan
Highlights: A novel point of care assay, namely an enhanced immuno-dot blot assay, was prepared by chitosan gold nanoparticle. This biosensor is designed for discrimination of anti-Toxoplasma IgG and anti-Toxoplasma IgM antibodies. We developed a sensitive and simple method for the naked-eye differentiation of T. gondii infection. Abstract: This study reports development of a novel point of care assay, namely an enhanced immuno-dot blot assay, for discrimination of anti- Toxoplasma IgG and anti- Toxoplasma IgM antibodies. This method has been designed based on formation of a sandwich complex between a gold nanoprobe (chitosan gold nanoparticle-anti-human IgG or anti-IgM) and anti- Toxoplasma lysate antigen (TLA) which holds anti-TLA antibodies, either IgG or IgM. Briefly, anti-human IgG or anti-IgM antibody was conjugated to chitosan gold nanoparticles via glutaraldehyde chemistry. Then, lysate antigen was immobilized on the surface of nitrocellulose membrane, which followed by addition of the sera sample and gold nanoprobes. The positive signals were readily detectable via observation with naked eye. This positive color change was further intensified via gold enhancement chemistry. The intensity of biosensor signal was proportional to the concentration of active antibodies on the surface of nanoparticles, titer of T. gondii antibodies in the sera samples and concentration of Toxoplasma lysate antigen coated on the nitrocellulose membrane. A minimum concentration to use the antibodies for conjugation, to detect titer of Toxoplasma IgG and IgM antibodies, and the concentration of TLA coated in nitrocellulose membrane were 0.5 mg/mL, 2 IU/mL, 10 IU/mL, and 20 μg/mL, respectively. This enhanced immuno-dot blot assay offers a simple diagnostic technique without expensive equipment requirement for distinguishing of anti- T. gondii IgM and IgG antibodies in field conditions, pregnant women, and immunocompromised patients.